La evaluación del proceso de enseñanza-aprendizaje de los alumnos/as del noveno año de educación básica al tercer año de bachillerato del Colegio Nacional Vicente Bastidas Reinoso de la parroquia Selva Alegre, cantón Saraguro, provincia de Loja, en el periodo 2008 – 2009”. Lineamientos alternativos. - Herrera Carrión, Elvia de Jesús (2009)
The present thesis research, rotates around the query: The processes of evaluation, assessment and qualification that the educational ones use in the fiscal school “Vicente Bastidas Reinoso", don’t respond to the expectations, necessities and students' interests that are formed in the Institution, for it, our intention makes reference to investigate the types, phases and parameters that are come completing in the facility of our reference and that they are good for qualification effects and certification. The work allows creating conscience in teachers on its educational exercise, it is justified, since, we benefit: my person, the institution, the interviewed population and the students. The general objective is: To contribute to the improvement of the evaluate processes that are completed in the School Vicente Bastidas Reinoso." The process makes reference to the Participative Research, it generates reflection - action - reflection, since the knowledge is not Elected people's attribute. In the analysis and discussion of results they are proven the hypotheses scientifically for the road of the demonstration. Conclusions were exposed in order to suggest recommendations to the authorities of the Institution, so that teachers improve their knowledge on this pedagogic category. To conclude, an alternative Proposal was designed that will allow to overcome the knots it has more than enough educational evaluation.